Endoplasmic Reticulum Stress and Oncomir-Associated Chemotherapeutic Drug Resistance Mechanisms in Breast Cancer Tumors - Mehdizadehtapeh, Leila; YERLİKAYA, PINAR OBAKAN (TUBITAK - The Scientific and Technological Research Council of Turkey, 2021)
Breast cancer, as a heterogenous malign disease among the top five leading causes of cancer death worldwide, is defined as by far the most common malignancy in women. It contributes to 25% of all cancer-associated deaths after menopause. Breast cancer is categorized based on the expression levels of cell surface and intracellular steroid receptors [estrogen, progesterone receptors, and human epidermal growth factor receptor (HER2)], and the treatment approaches frequently include antiestrogen, aromatase inhibitors, and Herceptin. However, the management and prevention strategies due to adverse side effects stress the patients. The unsuccessful treatments cause to raise the drug levels, leading to excessive toxic effects on healthy cells, and the development of multidrug-resistance (MDR) in the tumor cells against chemotherapeutic agents. MDR initially causes the tumor cells to gain a metastatic character, and subsequently, the patients do not respond adequately to treatment. Endoplasmic reticulum (ER) stress is one of the most important mechanisms supporting MDR development. ER stress-mediated chemotherapeutic resistance is very common in aggressive tumors. The in vitro and in vivo experiments on breast tumors indicate that ER stress-activated protein kinase R (PKR)-like endoplasmic reticulum kinase (PERK)- activating transcription factor (ATF4) signal axis plays an important role in the survival of tumors and metastasis. Besides, ER stress-associated oncogenic microRNAs (miRNAs) induce chemoresistance in breast tumors. We aimed to have a look at the development of resistance mechanisms due to ER stress as well as the involvement of ER stress-associated miRNA regulation following the chemotherapeutic regimen in the human breast tumors. We also aimed to draw attention to potential molecular markers and therapeutic targets.
Keywords: Endoplasmic Reticulum Stress; Unfolded Protein Response; Multidrug Resistance; Oncomir; Breast Cancer